2018
DOI: 10.21608/egyfs.2018.65834
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Cervical Canal Length and/ or a Bishop Score Assessment as a Predictor for Successful Induction of Labor

Abstract: Objectives:To compare transvaginal sonography for cervical length measurement and digital examination for Bishop score assessment in women undergoing labor induction at term. Patients and Methods:A prospective study involved 140 women subjected to induction of labor. Preinduction assessment of Modified Bishop score and transvaginal ultrasound measurement of cervical length was done. Results:One hundred and forty nulliparous women had CL <28 mm and modified Bishop score of ≥7; 84.8% (123/140) of them delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…This study demonstrated that pre-induction transvaginal cervical length measurement was a significant independent predictor of successful induction of labour (p<0.001). This was in agreement with previous studies which looked at the role of pre-induction cervical length assessment [ 11 , 14 , 16 20 ]. In addition, our analysis showed a high degree of correlation between cervical length and Bishop score with r -value of 0.745 ( p <0.001), hence providing evidence for the potential use of sonographic assessment of cervix as a method to predict successful induction.…”
Section: Discussionsupporting
confidence: 93%
“…This study demonstrated that pre-induction transvaginal cervical length measurement was a significant independent predictor of successful induction of labour (p<0.001). This was in agreement with previous studies which looked at the role of pre-induction cervical length assessment [ 11 , 14 , 16 20 ]. In addition, our analysis showed a high degree of correlation between cervical length and Bishop score with r -value of 0.745 ( p <0.001), hence providing evidence for the potential use of sonographic assessment of cervix as a method to predict successful induction.…”
Section: Discussionsupporting
confidence: 93%